Gigi tiruan sebagian lepasan sebagai benda asing dalam trakea (Removable partial denture as foreign body in trachea) - Sri Herawati JPB (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Foreign bodies in the trachea are not uncommon. Usually the patients come with dyspnea and a history of having aspirate something. This is an emergency case and needs extraction of the foreign body via bronchoscopy with general anesthesia as soon as possible. The optimal preparation is a controlled, well-equipped and well prepared operative setting. A case of removable partial denture as foreign body in trachea was reported and the extraction of the denture was done with difficulty due to the size of the denture compared with the width of the rima glottis and the trachea.